MRNA Vaccine Effectiveness Against Coronavirus Disease 2019 Hospitalization Among Solid Organ Transplant Recipients . (6th April 2022) - Kwon, Jennie H; Tenforde, Mark W; Gaglani, Manjusha; Talbot, H Keipp; Ginde, Adit A; McNeal, Tresa; Ghamande, Shekhar; Douin, David J; Casey, Jonathan D; Mohr, Nicholas M; Zepeski, Anne; Shapiro, Nathan I; et al.
Abstract: Background: The study objective was to evaluate 2- and 3-dose coronavirus disease 2019 (COVID-19) mRNA vaccine effectiveness (VE) in preventing COVID-19 hospitalization among adult solid organ transplant (SOT) recipients. Methods: We conducted a 21-site case-control analysis of 10 425 adults hospitalized in March to December 2021. Cases were hospitalized with COVID-19; controls were hospitalized for an alternative diagnosis (severe acute respiratory syndrome coronavirus 2-negative). Participants were classified as follows: SOT recipient (n = 440), other immunocompromising condition (n = 1684), or immunocompetent (n = 8301). The VE against COVID-19-associated hospitalization was calculated as 1-adjusted odds ratio of prior vaccination among cases compared with controls. Results: Among SOT recipients, VE was 29% (95% confidence interval [CI], −19% to 58%) for 2 doses and 77% (95% CI, 48% to 90%) for 3 doses. Among patients with other immunocompromising conditions, VE was 72% (95% CI, 64% to 79%) for 2 doses and 92% (95% CI, 85% to 95%) for 3 doses. Among immunocompetent patients, VE was 88% (95% CI, 87% to 90%) for 2 doses and 96% (95% CI, 83% to 99%) for 3 doses. Conclusions: Effectiveness of COVID-19 mRNA vaccines was lower for SOT recipients than immunocompetent adults and those with other immunocompromising conditions. Among SOT recipients, vaccination with 3 doses of an mRNA vaccine led to substantially greater protection than 2 doses. Abstract : Effectiveness of COVID-19 mRNA vaccines against COVID-19 hospitalization is lower for solid organ transplant (SOT) recipients compared with immunocompetent people and those with other immunocompromising conditions. Among SOT recipients, 3 vaccine doses lead to substantially greater protection than 2.